1986
DOI: 10.1038/clpt.1986.50
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroergotamine and mobilization after major orthopedic surgery

Abstract: The effects of dihydroergotamine (DHE) on the degree of mobilization and response to orthostatic stress after total hip arthroplasty were studied. In the mobilization study, 78 patients received DHE, 0.5 mg im, twice a day from the day of surgery until full mobilization was achieved. Eighty-four patients who received placebo served as controls. There was no significant difference in the time until the first day of mobilization or the degree of mobilization. In the orthostatic test condition, subgroups of 61 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In 4 studies 7,17,20,23 , orthostatic hypotension was defined as a drop in systolic and/or diastolic blood pressure following a change in body position (e.g., a drop of ≥20 mm Hg in systolic blood pressure and/or a drop of ≥10 mm Hg in diastolic blood pressure during standing compared with the supine position, as reported by Cheng et al 17 ). Arterial blood pressure was measured using a mercury manometer by the auscultatory method in 1 study 19 . Three studies used a beat-to-beat measurement of arterial blood pressure recorded noninvasively by photoplethysmography using finger cuffs 7,20,23 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 4 studies 7,17,20,23 , orthostatic hypotension was defined as a drop in systolic and/or diastolic blood pressure following a change in body position (e.g., a drop of ≥20 mm Hg in systolic blood pressure and/or a drop of ≥10 mm Hg in diastolic blood pressure during standing compared with the supine position, as reported by Cheng et al 17 ). Arterial blood pressure was measured using a mercury manometer by the auscultatory method in 1 study 19 . Three studies used a beat-to-beat measurement of arterial blood pressure recorded noninvasively by photoplethysmography using finger cuffs 7,20,23 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not report the follow-up time point for the incidence of an orthostatic hypotension event 19,21 . Duus et al 19 reported an incidence proportion of 16% (95% CI, 9% to 28%), and Kaplan et al 21 reported an incidence proportion of 23% (95% CI, 17% to 31%). The overall pooled incidence proportion of an orthostatic hypotension event for the unilateral THA population was 26% (95% CI, 19% to 33%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations